POTENSI PANAS BUMI DAERAH PANDEGLANG DAN SEKITARNYA BERDASARKAN EVALUASI DATA GEOLOGI DAN GEOFISIKA TERPADU - Subagio, Subagio; S.Widijono, Bambang (Pusat Survei Geologi, 2008)
Intergrated geological and geophysical informations provide ilustration of subsurface geology of the researched area. Result of gravity modelling of the study area show several grabbens and intrusives. This structures would probably be act as trap of a geothermal potential. The young intrusive rocks beneath the Gunung Karang is interpretated as a heat sources, while the Tertiary sedimentary rocks could possibly be a reservoir. The altered volcanic rocks widely exposed in the study area may presence as a caprock. The possibility of geothermal energy potential is also indicated by the area.occurrence of several of springs exposed in the area. Keywords: intergrated geophysical information, subsurface geological structure, geothermal